Treatment for painful calcified chronic pancreatitis: extracorporeal shock wave lithotripsy versus endoscopic treatment: a randomised controlled trial. Issue 4 (17th October 2006) - Dumonceau, Jean-Marc; Costamagna, Guido; Tringali, Andrea; Vahedi, Kouroche; Delhaye, Myriam; Hittelet, Axel; Spera, Gianluca; Giostra, Emiliano; Mutignani, Massimiliano; De Maertelaer, Viviane; Devière, Jacques
Abstract : Background: In chronic pancreatitis, obstruction of the main pancreatic duct (MPD) may contribute to the pathogenesis of pain. Pilot studies suggest that extracorporeal shock wave lithotripsy (ESWL) alone relieves pain in calcified chronic pancreatitis. Aim: To compare ESWL alone with ESWL and endoscopic drainage of the MPD for treatment of pain in chronic pancreatitis. Subjects: Patients with uncomplicated painful chronic pancreatitis and calcifications obstructing the MPD. Methods: 55 patients were randomised to ESWL alone (n = 26) or ESWL combined with endoscopy (n = 29). Results: 2 years after trial intervention, 10 (38%) and 13 (45%) patients of the ESWL alone and ESWL combined with endoscopy group, respectively, had presented pain relapse (primary outcome) (OR 0.77; 95% CI 0.23 to 2.57). In both groups, a similar decrease was seen after treatment in the MPD diameter (mean decrease 1.7 mm; 95% CI 0.9 to 2.6; p<0.001), and in the number of pain episodes/year (mean decrease, 3.7; 95% CI 2.6 to 4.9; p<0.001). Treatment costs per patient were three times higher in the ESWL combined with endoscopy group compared with the ESWL alone group (p = 0.001). The median delay between the onset of chronic pancreatitis and persistent pain relief for both groups was 1.1 year (95% CI 0.7 to 1.6), as compared with 4 years (95% CI 3 to 4) for the natural history of chronic pancreatitis in a reference cohort (p<0.001). Conclusions: ESWL is a safe and effective preferred treatment for selected patients with painful calcified chronic pancreatitis. Combining systematic endoscopy with ESWL adds to the cost of patient care, without improving the outcome of pancreatic pain.